Representasi Perilaku Bullying Serial Drama Korea True Beauty - Atril Miran Eri; Hastuti Hastuti; Muh. Rizal Ardiansah Putra (UNIVED PRESS, Universitas Dehasen Bengkulu, 2023)
The drama entitled True Beauty is a Korean drama produced by tvN which was released in 2020 directed by Kim Sang Hyub. In this study, researchers used Charles Sanders Peirce's theory of semiotic analysis. Charles Sanders Peirce's theory emphasizes that criminal behavior is not due to heredity, but social/social environmental factors. The purpose of this research is to represent bullying, which the researchers found that there are three types of bullying that occur in this drama, namely physical bullying, verbal bullying, and psychological bullying. The method used is to group signs based on scenes related to the representation of bullying in the drama, which is then explained in each type of bullying scene. The conclusion of the study was that students bullied Lim Ju Kyung and Han Go Won on the grounds that both Lim Ju Kyung and Han Go Won had ugly looks. So that students at the school carry out bullying in the form of slapping, grabbing, pushing, insulting, threatening, giving nicknames, and looking down on victims. These actions can cause the victim to become insecure, easily scared, and can even lead to suicide.